Examining the Utility of the Mammalian Methylation Array for Pan-Mammalian Analysis of Monozygotic Twinning - Jenny van Dongen; Charles E. Breeze; Twinning Genetics Consortium (Epigenomes)
Background/Objectives: Human identical twins are born at a rate of 3–4 per 1000 live births. Many other mammals also occasionally produce monozygotic twins, referred to as sporadic polyembryony. The underlying mechanisms are unknown. Through epigenome-wide association studies (EWAS), we identified a robust DNA methylation signature in somatic tissues from human monozygotic (MZ) twins, comprising 834 differentially methylated positions (MZ-DMPs). The results point to a connection between monozygotic twinning and early genome programming and enable new angles to study monozygotic twinning. Methods: The mammalian methylation array (MMA) measures 38,608 CpGs focusing on regions that are well-conserved across many mammalian species, allowing for pan-mammalian comparative epigenomic studies. Here, we successfully map human MZ-DMPs to probes of the mammalian methylation array across 157 mammalian genomes. Results: As expected, based on the modest probe overlap between Illumina 450k/EPIC and mammalian methylation array probes, only a subset of MZ-DMPs reside in conserved regions covered by the mammalian methylation array. These include probes mapping to NPAS3, KLHL35, CASZ1, and ATP2B2. Re-analysis restricting the original EWAS in humans to conserved MMA regions yielded additional MZ-DMPs, suggesting that more loci may be detected by application of the mammalian array to monozygotic twins. Conclusions: In conclusion, the mammalian methylation array may prove to be a promising platform to study whether a shared DNA methylation signature of sporadic polyembryony exists across diverse mammalian species. This may potentially point to shared underlying mechanisms.